Decision on Halal Certification of Food and Beverage Products Processed by UMKM Products in Tangerang City - Study of Religiosity, Regulation, and Branding - Aulia Ramadhan; Edy Yusuf Agung Gunanto (Jurnal Ilmiah Ekonomi Islam, 2021)
The city of Tangerang with the motto akhlakul karimah and the majority of the population is Muslim, which is 1,587,270 or 88.25%, so it pays great attention to the halalness of the products in circulation. The government requires that every product that enters, circulates, and is traded in the territory of Indonesia must be halal certified, including products of Micro, Small, and Medium Enterprises (MSMEs). There are 11,746 MSMEs in Tangerang City and the leading sectors that can be developed are the service sector and manufacturing industry. This study aims to determine the effect of economic factors, religiosity, socio-culture, regulation, and branding on the decision of MSMEs to carry out halal certification. This study uses primary data with a data collection method in the form of a questionnaire. The population in this study is UMKM which has been halal certified with the facilitation of the Tangerang City Government in 2019. The population is 100 MSMEs and 80 MSMEs are sampled. This study uses multiple linear regression analysis is processed using SPSS version 22. The results of the analysis of this study indicate that the most dominant variable partially has a positive and significant effect on the decision of MSMEs to carry out halal certification is branding. This proves that the halal label can be used as a good image for MSMEs to consumers. The variables that partially have a positive and significant effect on the decision of MSMEs to carry out halal certification, then, are religiosity and regulation. Meanwhile, the socio-culture and economy partially do not affect the decision of MSMEs to carry out halal certification. Simultaneously, the results obtained are that economy, religiosity, socio-culture, regulation, and branding affect the decision of MSMEs to carry out halal certification.